2009
DOI: 10.1109/tit.2009.2027577
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Information Games in Multiuser Channels With Correlated Jamming

Abstract: Abstract-We investigate the behavior of two users and one jammer in an additive white Gaussian noise (AWGN) channel with and without fading when they participate in a noncooperative zero-sum game, with the channel's input/output mutual information as the objective function. We assume that the jammer can eavesdrop on the channel and can use the information obtained to perform correlated jamming. We also differentiate between the availability of perfect and noisy information about the user signals at the jammer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…In the case of perfect CSI availability at the jammer, it has been shown that correlated jamming is optimal in point-topoint as well as multi-user and multiple input multiple output systems [13], [14]. We will demonstrate that the same is true in the case of SKG systems when α = 0.…”
Section: A Full Main Channel Csi At Eve: Correlated Jammingmentioning
confidence: 63%
“…In the case of perfect CSI availability at the jammer, it has been shown that correlated jamming is optimal in point-topoint as well as multi-user and multiple input multiple output systems [13], [14]. We will demonstrate that the same is true in the case of SKG systems when α = 0.…”
Section: A Full Main Channel Csi At Eve: Correlated Jammingmentioning
confidence: 63%
“…For simplicity, in the following, we assume that the legitimate users employ constant signalling X = Y = √ P. In the case of perfect CSI availability at the jammer, it has been shown that correlated jamming is optimal in point-to-point as well as multiuser and multiple input multiple output systems [30,31]. We will demonstrate that the same is true in the case of SKG systems when α = 0.…”
Section: Full Main Channel Csi At Mallory: Correlated Jammingmentioning
confidence: 86%
“…3, but note that this representation does not hold for the extensive game with perfect information in Section III. Solving for the Nash equilibrium in mixed strategies, we obtain the optimal strategies and equilibrium outcome exactly as shown in (10). We conclude this section by describing a refinement to the sequential equilibrium solution, which takes into account the possibility of opponents making small errors while executing their equilibrium strategies.…”
Section: Perfect Information Gamementioning
confidence: 99%